Pengaruh Kepercayaan Diri Terhadap Penampilan Tari - Shefriana Putri Pulungan; Anindra Guspa (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
This study aims to explore the influence of dancers' self-confidence on dance performance. Using a qualitative approach with phenomenological methods, this study involved in-depth interviews with four participants selected using purposive sampling. Data were analyzed using Interpretative Phenomenological Analysis (IPA) to understand the experiences and meanings given by the subjects regarding self-confidence in the context of dance. The results showed that motivation from the coach plays a significant role in increasing dancers' self-confidence, where the coach provides positive support and strategies to overcome anxiety. Furthermore, experience and thorough preparation are also proven to be key factors in building self-confidence. Dancers who have practiced well feel more prepared and able to overcome nervousness when performing. This study provides insight into the importance of self-confidence in dance performance and how coaches can contribute to the process, while emphasizing the need for acceptance of the performance results.